INSOMNIA - Abdul Samad, Nor Syazwani Binti; Ratep, Nyoman; Westa, Wayan (Bali Journal of Medical and Health Sciences; vol 1no1 2013, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 I nsomnia is o n e of the more c om m on c omp l a i n ts p a t i e nts p re s e nt to t h e ir p h y sici a n s. S le e p p r oblems a f f e c t up to on e - th i rd of a ll Am e ri c a ns, a nd the loss of w o rkpl a c e p r odu c t i vi t y . P a t i e nts with ac ute inso m nia g e n e r a l l y r e spond w e ll to v a rious s e d a t i ve h y p n ot i c medi ca t i ons, but c h r onic inso m nia is a dif fe r e nt c h a l l e n g e . P h y s i c ians a nd p a t i e nts m a y r a i se c on c e rns a bout the lon g - t e rm use of s e d a t i ve h y pnot i c medi ca t i ons. Ev e n in l i g ht of these c on ce rns, how e v e r, the c h r onic inso m nia r e mai n s, ostensib l y l e a ving the p h y sici a n f e w c hoi c e s. A number of p r om i sing nonph a rm ac ol o g ic st r a t e g ies a re a v a i l a ble that p h y s ici a ns ca n ea si l y i m plem e nt. Th r o u g h the use of s e lf r a t i ng ins t rum e nts a nd a sl e e p l o g , p h y sici a ns ca n b r i n g t h e sle e p p r oblem in t o b e t t e r fo c us a nd mon i tor the e f f ic a c y of c l i nic a l in t e rv e nt i ons. C e rt a in b e h a vior a l te c h niques, such a s sle e p h y gie n e , st i mu l us c ontr o l, a nd sle e p r e striction, ca n be e f f e c t i ve r e medi e s for c h r onic inso m nia. The use of c r a n i a l e le c t r ic st i mu l a t i on for inso m nia is a lso showing p r om i sing r e sul t s. Th r ou g h ca reful a ssessment a nd the a dopt i on of si m ple nonph a rm a c ol o g ic str a t e g ies, the p h y sici a n ’ s in t e rv e nt i ons m a y r e sult in a g ood n i g ht’s sl e e p.